Amylase Production by Bacillus subtilis SY134D Strain Under Submerged Fermentation: Production of Amylase (Biological Sciences - PJSIR, 2020)
Industrial important enzymes have traditionally been obtained by using submerged fermentation technology. Many organisms are able to produce these enzymes, but only a few of them exhibit satisfactory characteristics for industrial application. The ability of bacterial strains from the genus Bacillus to secrete large amounts of extracellular a-amylase has made them well suited for commercial production. Amylase production using Bacillus subtilis SY134D strain was conducted in flasks and bioreactor. In flasks, our results showed that soybean cake, beet pomace and tomato pomace were the best carbon source used in submerged fermentation (SmF) after 72 h of incubation. In bioreactor, the rates of air flow and agitation speed are important factors that affect oxygen transfer rate which influence on product formation. When the aeration rate was increased from 0.25 to 0.75 vvm, amylase production increased at the speed of agitation 100 and 200 rpm. The best enzyme yield 127 IU/mL was obtained at 0.25 vvm an aeration rate and 300 rpm agitation speed in a 3L Electro-lab bio-reactor.